2022
DOI: 10.15581/004.44.002
|View full text |Cite
|
Sign up to set email alerts
|

Percepciones docentes sobre observación entre iguales: resistencias, agencia, procedimiento y objetivos de mejora

Abstract: La investigación recoge las percepciones de docentes en una práctica de observación entre iguales como mecanismo para el desarrollo profesional. A partir de una observación colaborativa y mutua, 131 docentes acuerdan focos de observación y se observan mutuamente en una sesión de clase, ofreciéndose feedback para concretar objetivos personales de mejora. Los resultados pretest-postest indican disminución de las resistencias e incremento de algunas dimensiones de la agencia docente. Los análisis descriptivos mue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
(52 reference statements)
0
11
0
Order By: Relevance
“…Considering that RPO is based on collaboration, reciprocity, and equal relationship between teachers, it is expected that resistance to RPO may be reduced when teacher collaboration is promoted and institutions follow the recommended guidelines. Instead of the hierarchical orthodoxy that characterises assessment‐based types of classroom observation, relationships in RPO are more collegial in nature, which can help reduce anxiety or authoritative pressure (Alam et al., 2020; Corcelles‐Seuba, Duran, et al., 2023; O'Leary & Savage, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that RPO is based on collaboration, reciprocity, and equal relationship between teachers, it is expected that resistance to RPO may be reduced when teacher collaboration is promoted and institutions follow the recommended guidelines. Instead of the hierarchical orthodoxy that characterises assessment‐based types of classroom observation, relationships in RPO are more collegial in nature, which can help reduce anxiety or authoritative pressure (Alam et al., 2020; Corcelles‐Seuba, Duran, et al., 2023; O'Leary & Savage, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The pretest‐posttest study by Corcelles‐Seuba, Duran, et al. (2023) showed that teachers' participation in an RPO intervention reduced teachers' initial resistance to RPO, especially from teachers with no prior experience in PO. However, this study did not consider differences in terms of observer and observee, neither did it analyse the influence of demographic variables nor perception of school support and role performance.…”
Section: Introductionmentioning
confidence: 99%
“…From a collaborative approach to peer observation (Gosling, 2002(Gosling, , 2005(Gosling, , 2014, RPO can be defined as a pair or group of teachers working together as equal partners who agree to observe one or more pedagogical aspects of one another's practice. Following the main phases of the peer observation process-pre-observation, observation and feedback-teachers collect evidence of their practices to offer mutual and constructive feedback with the final goal of improving their teaching (Corcelles-Seuba et al, 2022;O'Leary & Savage, 2020).…”
Section: Reciprocal Peer Observationmentioning
confidence: 99%
“…Findings from previous empirical research indicate that RPO is a promising training strategy with numerous benefits for teachers' learning when they perform both roles, observee and observer (Corcelles‐Seuba et al., 2022; Duran et al., 2020; Rosselló & de la Iglesia, 2021). Observers can learn new teaching strategies by watching how a colleague manages a classroom (Hendry & Oliver, 2012; Motallebzadeh et al., 2017; Tenenberg, 2016; Thomson et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation